Serum folate deficiency and the risks of dementia and all-cause mortality: a national study of old age. Issue 2 (15th March 2022) - Rotstein, Anat; Kodesh, Arad; Goldberg, Yair; Reichenberg, Abraham; Levine, Stephen Z
Abstract : Background: The association between serum folate deficiency and the risk of dementia in old age is unclear, perhaps owing to small sample sizes, the competing risk of mortality or reverse causation. Objective: To examine the associations between serum folate deficiency and the risks of incident dementia and all-cause mortality in a large national sample of older adults. Methods: A prospective cohort aged 60–75 years (n=27 188) without pre-existing dementia for at least 10 years, was tested for serum concentrations of folate and followed up for dementia or all-cause mortality. Serum folate deficiency was classified as present (<4.4 ng/mL), otherwise absent. HRs and 95% CIs from competing risks Cox models were fitted to quantify the associations between serum folate deficiency and the risks of dementia and all-cause mortality. To examine reverse causation, the analysis was stratified by duration of follow-up. Findings: The presence compared with the absence of serum folate deficiency was associated with higher risks of dementia (HR=1.68; 95% CI 1.32 to 2.13; p<0.001) and all-cause mortality (HR=2.98; 95% CI 2.52 to 3.52; p<0.001). Evidence for reverse causation were moderate for dementia and mild for all-cause mortality. Conclusions: Serum concentrations of folate may function as a biomarker used to identify those at risk of dementia and mortality; however, reverse causation is likely. Further research is needed to examine the role of serum folate deficiency in dementia aetiology. Clinical implications: Serum folate deficiency in older adults requires monitoring and treatment for preventative measures and/or as part of implemented therapeutic strategies.